Mediating effect of cognitive appraisal and coping on anticipatory grief in family caregivers of patients with cancer: a Bayesian structural equation model study - Di Sun; Xu Zhang; Jiaojiao Li; Meishuo Liu; Lijuan Zhang; Jing Zhang; Mengyao Cui (BMC, 2024)
Abstract Background Anticipatory grief is common among family caregivers of cancer patients and may be related to caregiver burden, family resilience, psychological capital, cognitive appraisal, and coping strategies. The purpose of this study was to examine the mediating role of cognitive appraisal and coping strategies in the relationship between caregiver burden, family resilience, psychological capital, and anticipatory grief among caregivers of cancer patients. Methods This study surveyed from January to September 2023 among 265 caregivers of lung and breast cancer patients in two public hospitals. They completed measures of caregiver burden, family resilience, psychological capital, cognitive appraisal, coping, and anticipatory grief. AMOS software was used to model the data with Bayesian structural equation modeling. Results Bayesian structural equation modeling results showed that caregiver burden had a direct effect on anticipatory grief. The chain mediating effects for cognitive appraisal tendency and coping tendency between caregiver burden, family resilience, psychological capital, and anticipatory grief, respectively. Coping tendency acted as a mediator between psychological capital and anticipatory grief. Conclusions The relationships between caregiver burden, family resilience, and psychological capital with anticipatory grief are embedded in the mediating effects of cognitive appraisal and coping. Early identification and intervention for caregiver burden, family resilience, psychological capital, cognitive appraisal, and coping methods may prevent anticipatory grief in caregivers of cancer patients.